The concept of sympathy and its meaning for clinical psychology (Phenomenology, Humanities and Sciences, 2024)
The central goal of this work is to introduce de concept of sympathy to the psychology, considering the perspective of the meeting and the notion of dialogic. Thus, we bring the concept of empathy, proposing that these two concepts constitute a theoretical explanatory dyad whose result is the increase in the effectiveness of a therapeutic encounter in the psychological clinic. It ends by pointing out possible sympathetic postures of the therapist, as well as care regarding the influence exerted in the process of social influence in psychotherapy.
Keywords: Sympathy; empathy; Existenttialism; Clinical Psychology; Psychotherapy